2016
DOI: 10.4012/dmj.2015-278
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional accuracy of dental casting patterns created by 3D printers

Abstract: Contrary to widespread incise CAD/CAM, little is known about the dental application of 3D printing, especially the possibility of using 3D printing with organic material. The resin patterns of a full crown model were created by four types of 3D printers, a thermofusion device (CX), a digital light processing stereo-lithograph device (B9), a laser stereo-lithograph device (DW) and a multi-jet modeling device (PJ). The dimensional accuracy of the outer and inner diameters and depths of the created model crowns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 16 publications
1
61
1
4
Order By: Relevance
“…The regression analysis using the Weibull characteristic strength of the three bending tests showed that the coefficients of determination were very large, especially for the combination of the 4-point bending strength and biaxial flexural strength (the determination coefficient of the combination of the 3-point bending strength and 4-point bending strength was 0.888, that of the 3-point bending strength and biaxial flexural strength was 0.920 and that of the 4-point bending strength and the biaxial flexural strength was 0.991). These results also indicated that the biaxial flexural test is an effective valid test method for dental HRs with high filler content 18,19) , such as dental CAD/CAM hybrid resin, which was approved for use for premolars by the Japanese national health insurance program in 2014 [20][21][22] , and may be used to develop stronger HRs in the future.…”
Section: Discussionmentioning
confidence: 85%
“…The regression analysis using the Weibull characteristic strength of the three bending tests showed that the coefficients of determination were very large, especially for the combination of the 4-point bending strength and biaxial flexural strength (the determination coefficient of the combination of the 3-point bending strength and 4-point bending strength was 0.888, that of the 3-point bending strength and biaxial flexural strength was 0.920 and that of the 4-point bending strength and the biaxial flexural strength was 0.991). These results also indicated that the biaxial flexural test is an effective valid test method for dental HRs with high filler content 18,19) , such as dental CAD/CAM hybrid resin, which was approved for use for premolars by the Japanese national health insurance program in 2014 [20][21][22] , and may be used to develop stronger HRs in the future.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, there is a wide selection of different printers and manufacturers to choose from. Although MultiJet Printers are considered more accurate in comparison with SLA or DLP printers (Ishida & Miyasaka ), their investment costs are significantly higher. For a dental school, the most efficient solution seems to be a device which is suitable for creating educational models as well as for the production of applications in patient's care.…”
Section: Discussionmentioning
confidence: 99%
“…5 3D printing is a broad concept that can be classified as additive manufacturing. Common additive technologies applied in medicine include selective laser sintering, 12 fused deposition modeling, 13 multi-jet modeling, 14 stereolithography, 15 powder-based printing, 16 and robocasting. 17 All of these techniques can be used to rapidly fabricate products with specific shapes, well-defined internal structures, and highly interconnected porosities.…”
Section: Introductionmentioning
confidence: 99%